Agro-economic and ecological assessment of poultry abattoir sludge as bio-nutrient source for walnut plantation in low-fertility soil - Ozdemir, Saim; Ozdemir, Serkan; Yetilmezsoy, Kaan (WILEY, 2019)
Recycling of nutrient-rich organic wastes in agricultural or horticultural practices is one of the most sustainable methods for both waste management and soil amendment. In this regard, high nutrient-demanding horticultural crops can utilize a recycling route of organic wastes abattoir waste after appropriate processing for plantation. In this study, sustainable recycling of poultry abattoir sludge (PAS) was explored for the cultivation of walnut (Juglans regia L.) in low-fertility soil, considering agronomic, economic factors, and associated environmental impacts based on the energy use. Tree growth rates and leaf nutrient contents were evaluated in plants fertilized with the conventional method as control treatment and four different doses of PAS amendments. Results of economical assessment and cost analysis indicated that the PAS dose of 400 g N tree(-1) had the lowest cost and was determined as the most appropriate nutrient proportion for fertilization practices on walnut plantation in marginal land, and the use of PAS for fertilization resulted in about 65.4% savings in terms of present value evaluation based on three cultivation years. Findings of the present study clearly concluded that agronomic, economic, and ecological advantages of waste utilization, such as PAS application on walnut plantation, could significantly contribute to establish sustainable management and crop production alternatives for eco-efficient cultivation systems. (c) 2019 American Institute of Chemical Engineers Environ Prog, 38: e13225, 2019
Keywords: agro-economic; ecologic; environmental assessment; high pH soil; poultry abattoir sludge; walnut; SEWAGE-SLUDGE; MINERAL FERTILIZERS; DIGESTATE; PERFORMANCE; EFFICIENCY; WASTES; MANURE; YIELD; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology